Prehispanic agricultural hydraulics - Ravines, Rogger (1980)
In pre-Hispanic Peru, agriculture was indisputably one of the main productive activities and the land was the determining factor in its socio-economic articulation. In the several millennia that the process of Andean culture means, the ancient Peruvians developed a series of technical procedures, including those aimed at the efficient use and management of land and water. Since the emergence of the first complex societies, throughout the Andean territory there is evidence of hydraulic works aimed both at defending the banks of rivers (avoiding their breaks, diversions or floods), as well as channeling their waters, conserving them or storing them. in dams.